2013
DOI: 10.4049/jimmunol.1202749
|View full text |Cite
|
Sign up to set email alerts
|

Proteasomal Degradation of Herpes Simplex Virus Capsids in Macrophages Releases DNA to the Cytosol for Recognition by DNA Sensors

Abstract: The innate immune system is important for control of infections, including herpesvirus infections. Intracellular DNA potently stimulates antiviral IFN responses. It is known that plasmacytoid dendritic cells sense herpesvirus DNA in endosomes via TLR9, and that non-immune tissue cells can sense herpesvirus DNA in the nucleus. However, it remains unknown how and where myeloid cells, like macrophages and conventional dendritic cells, detect infections with herpesviruses. Here we demonstrate that the HSV-1 capsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
211
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 179 publications
(220 citation statements)
references
References 48 publications
7
211
1
1
Order By: Relevance
“…In contrast to AIM2, DNA recognition by IFI16 can occur in both the cytosolic and nuclear compartments. For example DNA which has been transfected, lentiviral DNA that has accumulated or herpesvirus DNA which has been exposed in the cytosol can be detected by cytosolic IFI16 [2,46,48] while DNA from nuclear viruses such as HCMV is detected in the nucleus [10,49]. As mentioned earlier, the NLS of IFI16 is required for the nuclear localisation of IFI16.…”
Section: Discovery Of Aim2 As a Dna Receptormentioning
confidence: 85%
See 1 more Smart Citation
“…In contrast to AIM2, DNA recognition by IFI16 can occur in both the cytosolic and nuclear compartments. For example DNA which has been transfected, lentiviral DNA that has accumulated or herpesvirus DNA which has been exposed in the cytosol can be detected by cytosolic IFI16 [2,46,48] while DNA from nuclear viruses such as HCMV is detected in the nucleus [10,49]. As mentioned earlier, the NLS of IFI16 is required for the nuclear localisation of IFI16.…”
Section: Discovery Of Aim2 As a Dna Receptormentioning
confidence: 85%
“…Alternatively, in cells such as macrophages, which are less permissive to viral infection, proteasomal degradation of viral capsids allows the release of viral DNA into the cytosol prior to nuclear delivery of the genome. This exposure of viral DNA activates cytosolic IFI16, which also leads to STING/TBK1 activation and IFN-b expression [48]. While STING and TBK1 are widely accepted to be activated following IFI16 stimulation, the details of the molecular events involved in their activation have yet to be unravelled.…”
Section: Discovery Of Aim2 As a Dna Receptormentioning
confidence: 99%
“…Recent studies explored these issues in other herpesvirus models, such as HSV-1 (12,13,15,17,51), KHSV (14,16), and EBV (10). Orzalli et al (15,51) found that during HSV-1 infection IFI16, which is required for induction of IRF-3 signaling in these cells, remains nuclear.…”
Section: Discussionmentioning
confidence: 99%
“…IFI16 displays multifaceted activity due to its ability to bind to various target proteins (i.e., transcription factors, signaling proteins, and tumor suppressor proteins) and to modulate various cell functions (9). In addition, IFI16 has been shown to bind to and function as a pattern recognition receptor (PRR) of virus-derived intracellular DNA and trigger the expression of antiviral cytokines via the STING/TBK1/IRF3 signaling pathway (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Although many different functions have been ascribed to IFI16 (and to other proteins of the PYHIN family), its role as an antiviral restriction factor has not yet been fully described.…”
mentioning
confidence: 99%
“…The focus here is on IFI16 in the STING pathway. IFI16 was demonstrated to associate with microbial DNA during different viral and bacterial infections and to interact with STING (25,31,64,65). In human THP1 cells differentiated with phorbol myristate acetate into a macrophage-like phenotype, it was demonstrated that IFI16, cGAS, and STING were all required for the stimulation of type I IFN expression by either human immunodeficiency virus type 1 (HIV-1) or Listeria monocytogenes (31,65).…”
Section: Interactions Between the Cgas-cgamp-sting Pathway And Other mentioning
confidence: 99%